2023
DOI: 10.1002/solr.202300358
|View full text |Cite
|
Sign up to set email alerts
|

The Stabilization of CsPbI3−xBrx Phase by Lowering Annealing Temperature for Efficient All‐Inorganic Perovskite Solar Cells

Abstract: All‐inorganic perovskites are a promising solution for the fabrication of thermally stable perovskite solar cells (PSCs) with remarkable performances. However, a high annealing temperature is required for the stabilization of the photoactive phase of CsPbI3, which represents a limiting factor for their potential scaling‐up and manufacturing at industrial scale. This work demonstrates a new process for the stabilization of CsPbI3‐xBrx perovskite at lower annealing temperature of 180°, based on a rational haloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Reprinted with permission. [68] Copyright 2023, Wiley-VCH GmbH. f ) Evolution of the crystal structure and space group of CsPbBr 3 single crystal with the InCl 3 dopant.…”
Section: Additive Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Reprinted with permission. [68] Copyright 2023, Wiley-VCH GmbH. f ) Evolution of the crystal structure and space group of CsPbBr 3 single crystal with the InCl 3 dopant.…”
Section: Additive Engineeringmentioning
confidence: 99%
“…Moreover, Montecucco and his team identified that DMAX (dimethylammonium xanthate) can also be employed to finetune the crystallization process of all-inorganic perovskite by lowering the annealing temperature, showcasing the versatility and effectiveness of this approach in diverse contexts (Figure 3e). [68] Mai et al showed that the introduction of the inorganic indium chloride ion (InCl 3 ) dopant into the lattice structure of inorganic CsPbI 2 Br can also help to inhibit the formation of the yellow phase (Figure 3f ). [69] This modification enables AIWPSCs to maintain their efficiency for up to 80 h in ambient air without any degradation.…”
Section: Additive Engineeringmentioning
confidence: 99%